2014
DOI: 10.1111/mmi.12628
|View full text |Cite
|
Sign up to set email alerts
|

Rhodobacter capsulatusDprA is essential for RecA‐mediated gene transfer agent (RcGTA) recipient capability regulated by quorum‐sensing and the CtrA response regulator

Abstract: SummaryGene transfer agents (GTAs) are genetic exchange elements that resemble small DNA bacteriophages that transfer random pieces of the producing cell's genome to recipient cells. The best-studied GTA is that of Rhodobacter capsulatus, termed RcGTA. We discovered that the putative response regulator CtrA, which is essential for RcGTA production, is required for RcGTA-mediated gene acquisition, and confirmed that a RecA homologue is required. It was also discovered that a DprA (DNA-protecting protein A) homo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
50
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(53 citation statements)
references
References 75 publications
(190 reference statements)
1
50
0
Order By: Relevance
“…DprA, which preferentially binds ssDNA (7,37,40) and physically interacts with SsbB and RecA in vivo (5) and with RecA in vitro (7,8,41,42), has two activities: to mediate annealing of two complementary strands coated by SsbB and to a lesser extent by SsbA or naked ssDNA and to recruit RecA⅐dATP onto SsbB-or SsbA-coated ssDNA (7). The first activity is required for the annealing of the incoming oligomeric plasmid ssDNA to reconstitute a dsDNA circular plasmid molecule (plasmid transformation) (7).…”
Section: Discussionmentioning
confidence: 99%
“…DprA, which preferentially binds ssDNA (7,37,40) and physically interacts with SsbB and RecA in vivo (5) and with RecA in vitro (7,8,41,42), has two activities: to mediate annealing of two complementary strands coated by SsbB and to a lesser extent by SsbA or naked ssDNA and to recruit RecA⅐dATP onto SsbB-or SsbA-coated ssDNA (7). The first activity is required for the annealing of the incoming oligomeric plasmid ssDNA to reconstitute a dsDNA circular plasmid molecule (plasmid transformation) (7).…”
Section: Discussionmentioning
confidence: 99%
“…Genetic analysis showed that one of these genes, dprA, is essential for RcGTA recipient capability, as is the RecA homologue (13). These findings indicated that RcGTA-carried DNA recombines into the chromosome of recipient cells via a natural transformation-like mechanism rather than one resembling temperate phages (20,21).…”
mentioning
confidence: 75%
“…Instead, ComM homologues are detectable only in genomes in which the corresponding DprA homologue contains a DprA domain 3 (DD3) (see Fig. S1), which is predicted to confer dsDNA binding capability to DprA proteins (13). Based on these analyses, we speculate that ComM is involved in a recombination step within the cytoplasm of recipient cells, and that its function is related to the DD3 (13,18).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations